Risk factors for shoulder injuries in handball: systematic review - Stelios Hadjisavvas; Michalis A. Efstathiou; Vivian Malliou; Christoforos D. Giannaki; Manos Stefanakis (BMC, 2022)
Key points Several risk factors for shoulder injuries were identified specifically in handball players Isometric external rotation strength was the only modifiable risk factor supported by strong evidence. Further research is required as only 50% of the studies were of high quality Future studies should address the multifactorial nature of shoulder injuries in handball.